Aspidistra sonlaensis (Asparagaceae, Nolinoideae), a new species from northern Vietnam - Trinh, Ngoc Bon; Pham, van The; Nguyen, Thanh Son; Do, Thi Thanh Ha; Nguyen, Khang Sinh; Anh, Le Tuan; Nuraliev, Maxim S.; Vislobokov, Nikolay A. (Phytotaxa, 2021)
A new species of Aspidistra, A. sonlaensis, is described and illustrated from Son La Province in northern Vietnam. The new species is morphologically close to A. micrantha, but differs in number of perigone lobes, anther position and pistil shape. The new species is accessed as Data Deficient (DD) according to the IUCN categories and criteria.